2012
DOI: 10.1186/1471-2369-13-84
|View full text |Cite
|
Sign up to set email alerts
|

A case of rapidly progressive IgA nephropathy in a patient with exacerbation of Crohn’s disease

Abstract: BackgroundIgA nephropathy has been reported as a renal involvement in Crohn’s disease. Crescentic IgA nephropathy, which accounts for fewer than 5% of cases of IgA nephropathy, has a poorer prognosis than other forms of crescentic glomerulonephritis. We recently experienced a case of rapidly progressive IgA nephropathy concurrent with exacerbation of Crohn’s disease.Case presentationAn 18-year-old male diagnosed with Crohn’s disease underwent a hemicolectomy 2 years prior previously. He had maintained a state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…This is in contrast to case reports of adalimumab-induced IgAN where renal recovery was observed following withdrawal of adalimumab and commencement of an alternate immunosuppressive regimen 8 13 15. This finding would suggest that patients with adalimumab-induced IgAN may be a distinct subset of IgAN and these patients may have a markedly different response to immunosuppression compared with idiopathic IgAN 11 12…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This is in contrast to case reports of adalimumab-induced IgAN where renal recovery was observed following withdrawal of adalimumab and commencement of an alternate immunosuppressive regimen 8 13 15. This finding would suggest that patients with adalimumab-induced IgAN may be a distinct subset of IgAN and these patients may have a markedly different response to immunosuppression compared with idiopathic IgAN 11 12…”
Section: Discussioncontrasting
confidence: 64%
“…IgAN has been recognised as a rare complication of CD. However, this usually occurs among patients with poorly controlled CD 11 12. Thus, this was felt to be less likely in our patient, who had stable disease since commencing adalimumab.…”
Section: Differential Diagnosismentioning
confidence: 84%
“…However, IL-17 was absent in renal tissue with primary IgAN. These findings suggest the simultaneous involvement of IL-17 in both worsening intestinal inflammation and enhancing rapidly progressive IgAN development in CD patients [24]. Interestingly, wang J et al have revealed in their experimental studies the etiology behind IgAN in IBD patients, highlighting the critical role of LIGHT, a TNF-α super family member and keystone mediator in the pathogenesis of CD [26] [27].…”
Section: Glomerulonephritis (Gn)mentioning
confidence: 96%
“…Patients with IgAN often develop proteinuria and hematuria with deterioration of renal function. Recent clinical studies have demonstrated that IgAN appears concurrently with the onset or exacerbation of IBD, mainly CD [23] [24]. However, the connection between the impaired mucosal immunity and the progression of IgAN is still unclear.…”
Section: Glomerulonephritis (Gn)mentioning
confidence: 99%
“…They described both clinical and pathologic remission of kidney disease concomitant with the treatment of symptoms of intestinal disease. Nineteen subsequent case reports in the literature have described IgAN in IBD (9,22,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). A majority of these patients had IgAN during onset or exacerbation of IBD, as well as clinical remission of kidney disease in conjunction with successful treatment of bowel inflammation.…”
Section: Discussionmentioning
confidence: 99%